Effect of self-willed crowding period on stall position and performance in Czech Fleckvieh cattle - Miljan, Erbez; Egil, Bøe Knut; Falta, Daniel; Chádlek, Gustav (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2010)
The aim of this research was to investigate cow’s behaviour during crowding period and its influence on daily milk yield (DMY). Cows were self-willed crowded probably as a result of arthropod ectoparasites infestation and high summer temperatures. In this research 18 cows were divided in two groups based on the previous 5-day-observation of stall position. Our hypothesis was that the cows more frequently standing in feeding fence (FF) are higher ranked than those standing more frequently in dunging passage (DP). With green colour we marked 9 cows standing in feeding fence and named as GREEN group, and 9 cows standing in dunging passage with blue colour and named as BLUE group. Cows were observed totally 3 consecutive days, from 12 midday to 16 p.m. in period of intensive crowding from August 6 to 8. Attendance of GREEN and BLUE groups in both parts was estimated 24 times (2 observations/hour). Cows were monitored by two network cameras of VIVOTEK technology. In this research it was found that GREEN cows spend more time in FF part, totally 57.5% compared to 42.5%. In BLUE group so high difference in attendance in FF or DP part was not found, but attendance in DP part was slightly higher (54.2% compared to 45.8%). GREEN group had the same milk production as another group (27.48 kg compared to 22.61 kg, p > 0,1281).